Pokdarwis Dewi Sri Contribution in Development Sendangsari Tourism Village, Wonosobo - Maryetti; Marya Yenny; Reni Sulistyowati; Rd Rita Ritasari; Taufiqurrahman Hafy (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This study aims to determine the contribution of the local community and the government to the development of tourism in Sendangsari Village, to discuss the government's steps in mobilizing the community to develop tourism, and to find out the tourism potentials in Sendangsari Village. Research methods: In this study, researchers used descriptive qualitative research with data collection techniques using observation and interviews from several informants related to tourism development in the Sendangsari Tourism Village. To obtain information, researchers used a purposive sampling technique. Results and discussion: The benefits that are expected from this research are to be able to add insight and experience that researchers have gained while undergoing lectures and add new insights and knowledge about tourism for the community and local government in developing tourism in Sendangsari Village. The results of this study show the contribution of local communities to tourism development in the Sendangsari Tourism Village by becoming local guides, homestay providers, souvenirs, culinary delights and assisting in tourism village promotion activities. Implications: Sendangsari Village is located at an altitude of 1013 meters above sea level and has temperatures ranging from 18°-28°C so it is suitable for tourists who want to travel here. In addition, Sendangsari Tourism Village also has tourist attractions that can be visited such as cultural tourism, nature tourism, agro tourism, and live-in. The government's role in mobilizing the community in Sendangsari Village is quite optimal because the government helps in financing facilities and infrastructure and provides guidance to tourists in Sendangsari Village Keywords: Sendangsari Tourism village, Community Contribution, Tourism Development